KADAR KALSIUM (Ca) DALAM CAIRAN KREVIKULAR GINGIVA PADA PENDERITA PERIODONTITIS KRONIS - Ita Kurniawati; Peni Pujiastuti; Agustin Wulan Suci Dharmayanti (Odonto : Dental Journal, 2015)
Background: Chronic periodontitis occurred mostly in productive ages. Chronic periodontitis was started by adherence and accumulation of plaque bacteria that caused vascular enhancement, PMN infiltration, and periodontal tissue destruction. This process caused bone calcium solubitily which went trough blood stream and excreted to gungiva sulci. Calcium in periodontal tissue could be found both in extracellular and intracellular matrix.Purpose: Purpose of this study was to know calcium level in gingival crevicular fluid of chronic periodontitis and compare calcium level in chronic periodontitis and gingivitis.Method: This study was analytic observational with cross sectional approach and got admission from ethic comission of Dental Faculty, Gadjah Mada University. The subjects were patients who came to dental hospital of Jember University. The subjects had to full fill informed consent. The subjects were selected according inclusion and exclusion criteria. Subjects  complying inclusion criteria were divided into gingivitis group (PI score 0 - 0.7) and chronic periodontitis (PI score 1 - 8.0). Gingival crevicular fluid samples were collected from teeth which got gingivitis and chronic periodontitis, GCF was absorbed using paperpoint and stored inside eppendorf tube. Paperpoint was added with 50 µL 0.02 M PBS pH 7.4 and 100 µL distilled water. Calcium level was measured by Atomic Absorption Spectrophotometer (AAS). Result: The result showed there was calcium in gingival crevicular fluid of chronic periodontitis. Mean of calcium level of chronic periodontitis was higher than  gingivitis.Conclusion: This study concluded there was calcium in gingival crevicular fluid of chronic periodontitis and calcium level of chronic periodontitis was higher than gingivitis.